Thermodynamic assessment of the ordered B2 phase in the Ti-V-Cr-Al quaternary system - Wang, H; Warnken, N; Reed, R (2011)
Thermodynamic assessment of the ordered B2 phase in the quaternary Ti-V-Cr-Al system is carried out. A set of self-consistent thermodynamic parameters is presented. A two-sublattice model (Al,Cr,Ti,V )0.5: (Al,Cr,Ti,V )0.5 is used. The predicted phase equilibria and order/disorder transformation temperature are in good agreement with experimental information, both in the Ti-V-Cr-Al quaternary and in the important binary and ternary subsystems. The thermodynamic dataset can be used to predict compositions which are prone to the order/disorder reaction. © 2011 Elsevier Ltd. All rights reserved.